Estrategia de comunicación integral de mercadotecnia para una ONG con enfoque educativo (Integrated marketing communication strategy for an NGO with educational approach). - Dávila Ruiz, Diana; Sibaja Ramírez, Ruviel (Facultad de Contaduría Pública y Administración U.A.N.L., 2014)
Abstract. Alianza Para La Educación México A.C is a non-governmental, non-profit organization founded in 2008 and established in Monterrey, Nuevo Leon, México. Its mission is to be an agent of change in society working with individuals and institutions, providing resources and tools for students living in adverse economic conditions, so they can have access to college and postgraduate education. The need to attract more donations is imperative considering that each year new students are integrated into the program and the costs are becoming more difficult to cover. This research aims to develop an integrated marketing communication strategy with the purpose of helping the organization to raise funds. The research methodology consisted of several deep interviews to different audiences related to the work of the organization, the audiences were: private foundations, individuals as donors, corporate social responsibility offices from well-known companies, and college students awarded with scholarships. The main recommendations for the organization derived from this research are: to have an active board of directors, the development and implementation of a website where donors can monitor the performance of the organization through general reports, to implement a public relations program that will allow to expand the efforts through strategic alliances, and to raise awareness among the students about the importance of giving back to Alianza para la Educación México A.C. Resumen. Alianza para la Educación México A.C. es una organización no gubernamental fundada en 2008 y establecida en Monterrey, Nuevo León. Su misión es ser un agente de cambio en la sociedad colaborando tanto con individuos como con instituciones, ofreciendo recursos y herramientas a personas que viven en condiciones económicas adversas, para que tengan acceso a una oportunidad educativa de nivel superior y de posgrado. La necesidad de captar más donativos es imperante considerando que cada año nuevos estudiantes se integran al programa y los costos son cada día más difíciles de cubrir. Esta investigación tiene el objetivo de desarrollar una estrategia de comunicación integral de mercadotecnia que ayude a la organización a recaudar fondos. La metodología consistió en la aplicación de entrevistas a profundidad a diferentes audiencias (ONG´s en su rol de donadoras, personas físicas donantes, personas morales donantes y alumnos beneficiados por becas) para definir la estrategia más asertiva para la recaudación de fondos. Las principales recomendaciones para la organización derivadas de esta investigación son: tener un consejo administrativo activo, desarrollar e implementar mecanismos que le permitan a los donantes monitorear los reportes de resultados de la organización, activar un programa de relaciones publicas que permita generar alianzas para la recaudación de fondos y sensibilizar a los becados beneficiados en ser futuros donantes.